Analisis Sentimen Masyarakat Terhadap Fenomena Childfree (Kehidupan Tanpa Anak) Pada Twitter Menggunakan Algoritma Naïve Bayes - Erizal, Erizal; Hasan, Firman Noor (Journal of Information System Research (JOSH), 2024)
Childfree is a phenomenon that occurs not only in the world but also in Indonesia. There are many negative and positive stigmas that arise regarding the phenomenon of living a life without children, especially in urban areas. The public's response to the childfree phenomenon, especially in urban areas in Indonesia, is varied, and is more influenced by various factors. In this research, we analyzed netizens' views on the childfree phenomenon using the Naïve Bayes method assisted by rapidminer tools to process text data collected via social media X. The aim of this research is to analyze and present data regarding public sentiment towards the childfree phenomenon in Indonesia. The results of the research found that 319 referred to negative sentiment, and only 181 referred to positive sentiment. The accuracy results produced by the Naïve Bayes algorithm were 95.02%. Showing that the childfree phenomenon is chosen by some netizens, especially in urban areas, because they want young people to focus on education and careers in order to make their lives more stable.